2019
DOI: 10.2147/cmar.s180242
|View full text |Cite
|
Sign up to set email alerts
|

PUF60 accelerates the progression of breast cancer through down-regulation of PTEN expression

Abstract: BackgroundPUF60 is a splicing variant of far upstream element binding protein 1-interacting repressor, which is abnormally expressed in a variety of tumors and is closely involved in their progression. However, whether PUF60 participates in the occurrence and development of breast cancer remains unknown. Therefore, the objective of the current study is to explore the effects and mechanism of PUF60 in the progression of breast cancer.MethodsPUF60 expression patterns in breast cancer tissues and cells were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…PUF60 is essential, and heterozygous loss of function causes Verheij syndrome, which is characterized by severe developmental abnormalities in most patients ( Low et al, 2017 ; Verheij et al, 2009 ). PUF60 is also involved in Hepatitis B virus infection ( Sun et al, 2017 ) and cancer progression ( Sun et al, 2019 ). In C. elegans , we found a G281D amino acid substitution in rnp-6 lying within the second RNA binding motif at a position conserved across evolution ( Figure 1D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PUF60 is essential, and heterozygous loss of function causes Verheij syndrome, which is characterized by severe developmental abnormalities in most patients ( Low et al, 2017 ; Verheij et al, 2009 ). PUF60 is also involved in Hepatitis B virus infection ( Sun et al, 2017 ) and cancer progression ( Sun et al, 2019 ). In C. elegans , we found a G281D amino acid substitution in rnp-6 lying within the second RNA binding motif at a position conserved across evolution ( Figure 1D ).…”
Section: Resultsmentioning
confidence: 99%
“…Because PUF60 is involved in various human diseases ( Sun et al, 2019 ; Sun et al, 2017 ; Xu et al, 2018 ), we next explored the potential role of rnp-6 in imparting immunity in higher organisms. We first asked if PUF60, the mammalian homolog of rnp-6 , is regulated during infection.…”
Section: Resultsmentioning
confidence: 99%
“…Poly-U binding splicing factor 60 kDa (PUF60), a factor regulating RNA splicing, is closely involved in tumor progression. The expression of PUF60 was highly correlated with TNM staging and lymph node metastasis in breast cancer (Sun et al, 2019b). Kobayashi et al (2016) detected PUF60 auto-antibodies in the sera of early-stage colon cancer patients and concluded that it may be a candidate biomarker for the diagnosis and prognosis of colon cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, we demonstrated that PUF60 could promote RCC cell growth through mediating TERT signaling in vitro and in vivo. It has been reported that PUF60 has tumor promoting effects in breast cancer [49], but it remains to be investigated whether this effect of PUF60 depends on TERT signaling. According to our experimental data in Fig.…”
Section: Discussionmentioning
confidence: 99%